Confesiones y silencios a través de la pluma: relaciones entre escribanos y otorgantes en Cuenca, Ecuador (siglo XVIII) - Arteaga, Maria Teresa (2025)
The article offers an overview of the Notarial Fund of the National Historical Archive, shaped by a diversity of manuscripts associated with the wills and decisions of the grantors during the 18th century in Cuenca, Ecuador. The relationship between scribes and grantors is a constant theme, revealing dialogues, questions, answers, confessions, and silences that gradually constructed meanings and images intended for both the present and posterity. The practice of notarial work was not only marked by a moral and ethical authority, limited to certifying or attesting to goods and property, but also established specific dynamics between notaries and grantors. Finally, the findings show that the notarial offices served as spaces for the circulation of people, goods, documents, and meanings, which allowed the grantors to either strengthen or negotiate their position of enunciation as they accessed literate culture.